2009
DOI: 10.1038/ki.2009.383
|View full text |Cite
|
Sign up to set email alerts
|

The use of continuous renal replacement therapy in series with extracorporeal membrane oxygenation

Abstract: A large percentage of patients on extracorporeal membrane oxygenation (ECMO) require continuous renal replacement therapy (CRRT) usually performed through a different venous access or by introducing a filter into the ECMO circuit. Here, we evaluated the efficacy and safety of including a CRRT machine in the circuit by connecting its inlet line after the centrifugal pump and its outlet line before the oxygenator. We tested the function of the combined system initially in a closed circuit, followed by an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 8 publications
2
77
1
2
Order By: Relevance
“…La técnica en línea tiene la ventaja de permitir un volumen de cebado más pequeño en comparación con el empleado cuando se suma el circuito de la máquina de TRRC. Pero también tiene desventajas: las bombas de infusión son incapaces de contener la filtración, no se monitorizan las presiones en el circuito de hemofiltración y la coagulación o la rotura del filtro no se pueden detectar tempranamente 3 . El control de la ultrafiltración puede ser especialmente deficiente cuando se requiere ultrafiltrar más de 800 ml en 24 h 17,21 .…”
Section: A Través De Un Hemofiltro En Líneaunclassified
See 1 more Smart Citation
“…La técnica en línea tiene la ventaja de permitir un volumen de cebado más pequeño en comparación con el empleado cuando se suma el circuito de la máquina de TRRC. Pero también tiene desventajas: las bombas de infusión son incapaces de contener la filtración, no se monitorizan las presiones en el circuito de hemofiltración y la coagulación o la rotura del filtro no se pueden detectar tempranamente 3 . El control de la ultrafiltración puede ser especialmente deficiente cuando se requiere ultrafiltrar más de 800 ml en 24 h 17,21 .…”
Section: A Través De Un Hemofiltro En Líneaunclassified
“…El uso de terapia de reemplazo renal continua (TRRC) en pacientes en ECMO mejora el equilibrio hídrico, resuelve desequilibrios electrolíticos, mejora el aporte calórico y reduce la necesidad de diuré-ticos 3 .…”
unclassified
“…Santiago et al reported that this last option is safe and effective in controlling both nitrogenous waste and the water balance without incurring any additional risks to the patient [19,20].…”
Section: Interaction Between the Rrt And Ecmo Circuitmentioning
confidence: 99%
“…First, if an ultrasonic probe is not placed to measure the flow, the blood flow through the hemofilter will remain unknown. Second, the infusion pumps are not accurate when they are used to prevent fluid loss in a high-pressure system [18,19] and can generate a large discrepancy between the desired and actual ultrafiltrate volumes. The third option involves the use of a dialysis machine that is connected to the circuit.…”
Section: Interaction Between the Rrt And Ecmo Circuitmentioning
confidence: 99%
“…This, in turn, can predispose to the potential life-threatening hemolysis, disseminated intravascular coagulation and enhanced systemic inflammation. The hemolysis through the medium of hemoglobinuria can precipitate renal injury [2,3]. …”
Section: Technical Aspects Of Combining Ecmo and Crrtmentioning
confidence: 99%